Automatic variance control and variance estimation loops - Moir, TJ (Springer Verlag (Germany) (for Birkhäuser Boston), 2001)
A closed-loop servo approach is applied to the problem of controlling and estimating variance in nonstationary signals. The new circuit closely resembles, but is not the same as, automatic gain control, which is common in radio and other circuits. The closed-loop nature of the solution to this problem makes this approach highly accurate, and it can be used recursively in real time.
Keywords: Automatic gain control; Variance estimation; Closed-loop control; Adaptive filters